EFEKTIVITAS AROMATERAPI MINYAK KETUMBAR (Coriander Essensial Oil) TERHADAP INTENSITAS MUAL MUNTAH PADA IBU HAMIL TRIMESTER I - Falenzah, Julian; Utami, Sri; Herlina, Herlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Nausea and vomiting are common symptoms often found in the first trimester of pregnancy. One non-pharmacological management that can reduce nausea and vomiting in pregnant women is aromatherapy coriander oil. The purpose of this study was to determine the effectiveness coriander oil aromatherapy on the intensity of nausea and vomiting in pregnant women with a quasy experiment research design. The sample of this study were 34 respondents taken by purposive sampling technique which was divided into 2 groups: 17 experimental respondents who were given coriander oil aromatherapy for 3 consecutive days and 17 control group respondents who were not given coriander oil aromatherapy. Measuring instruments used were PUQE questionnaire sheets and observation sheets with measurements the intensity of nausea and vomiting pre test on the first day and post test for 3 consecutive days after using coriander oil aromatherapy. Data analysis in this study uses Wilcoxon and Mann Whithey alternative tests. The results of this study showed that there were significant differences in the mean intensity of pre-test and post-test nausea in the experimental group with a p value of 0,000 and in the control group no difference was found with a p value of 0.691. While the results of tests conducted on the experimental group given aromatherapy with the control group without aromatherapy obtained p value of 0,000. The use coriander oil aromatherapy is effective in reducing the intensity of nausea and vomiting in first trimester pregnant women. Therefore, this study is suggested to be an alternative therapy for first trimester pregnant women to overcome the problem of nausea and vomiting during pregnancy. Keywords: aromatherapy, nauseous vomit, pregnancy